Mathematical Communication Skills in Solving Limit and Continuity Problems: Reviewed from Intra-and-Interpersonal Intelligence - Tyaningsih, Ratna Yulis; Arjudin, Arjudin; Salsabila, Nilza Humaira (Indonesian Journal of Science and Mathematics Education, 2022)
The various intelligence of students allows for differences in the mathematical communication skills produced. This study aimed to analyze students’ mathematical communication skills in terms of intrapersonal and interpersonal intelligence. The subjects of this study were students of Mathematics Education Class IV at the University of Mataram. This research method is descriptive with a survey design. This study uses a qualitative approach with stages covering problem formulation, sample selection, research limitations, instrumentation in the form of questionnaires and tests, data collection and analysis, and conclusion. The results of this study indicate that the level of intrapersonal and interpersonal intelligence affects students’ mathematical communication skills. This can provide information to educators to provide appropriate services.